Review : Metode Peningkatan Kelarutan Dengan Dispersi Padat - Elpa Giovana Zola; Salman Umar; Erizal Zaini (Journal of Pharmaceutical and Sciences, 2023)
One or more active chemicals are dispersed in a matrix or carrier in an inert state using a solid dispersion technique. The term "solid dispersion" describes the solid state in which a material is mixed with another material. Solid dispersions have many benefits over other traditional compositions and can be manufactured in a variety of ways. A combination of a hydrophobic matrix and a hydrophilic medication is called a solid dispersion. Drugs in solid dispersions can be dispersed in the form of molecules, amorphous solids, or crystals. The carrier used in solid dispersion systems is a polymer. The drug fills the gaps between the chains of polymers and increases their relative flexibility when the medication and polymer contact. Low rates of solubility and absorption are caused by chemicals that are powerful but not very soluble in water, thus affecting the effectiveness of therapy. Therefore, solubility is a crucial factor to consider while creating high-quality, safe, and effective preparations. A common technique to improve dissolution and solubility is the solid dispersion of active drug ingredients. Solid dispersions can be made in several methods to improve solubility and dissolving rate such as Dropping Method, Spray Drying Co-grinding, Lyophilization Technique, Fusion Method, Kneading, and Solvent Evaporation. Various types of carrier polymers that can be used to make solid dispersions are also covered in this study. The results of the review article show that the dissolution and solubility rate of active drug ingredients can be increased using the solid dispersion method compared to pure active ingredients.